2018
DOI: 10.1016/j.yjmcc.2017.12.013
|View full text |Cite
|
Sign up to set email alerts
|

ErbB2 promotes endothelial phenotype of human left ventricular epicardial highly proliferative cells (eHiPC)

Abstract: The adult human heart contains a subpopulation of highly proliferative cells. The role of ErbB receptors in these cells has not been studied. From human left ventricular (LV) epicardial biopsies, we isolated highly proliferative cells (eHiPC) to characterize the cell surface expression and function of ErbB receptors in the regulation of cell proliferation and phenotype. We found that human LV eHiPC express all four ErbB receptor subtypes. However, the expression of ErbB receptors varied widely among eHiPC isol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 63 publications
0
9
0
Order By: Relevance
“…Transcriptomic analysis of bona fide iPSC-ECs on the final day of differentiation identified four distinct populations of iPSC-ECs, noted by enriched expressions of CLDN5, APLNR, GJA5, and ESM1 respectively. Regulation of various signaling pathways controls biological and physiological functionality of endothelial cells 36,37 . Likewise, the identified iPSC-EC subpopulations displayed enriched expression of genes that together indicate specialized biological functions as metabolically active (CLDN5+), immune-responsive (APLNR+), arterial (GJA5+), and activated (ESM1+) ECs.…”
Section: Discussionmentioning
confidence: 99%
“…Transcriptomic analysis of bona fide iPSC-ECs on the final day of differentiation identified four distinct populations of iPSC-ECs, noted by enriched expressions of CLDN5, APLNR, GJA5, and ESM1 respectively. Regulation of various signaling pathways controls biological and physiological functionality of endothelial cells 36,37 . Likewise, the identified iPSC-EC subpopulations displayed enriched expression of genes that together indicate specialized biological functions as metabolically active (CLDN5+), immune-responsive (APLNR+), arterial (GJA5+), and activated (ESM1+) ECs.…”
Section: Discussionmentioning
confidence: 99%
“…With this study identifying a model of vascular toxicity instead of cardiac myocyte toxicity, we have a model to further test the efficiency of cell-based therapies to restore endothelial cell number and vascular function. Our group has previously isolated highly proliferative cells from epicardial left ventricular biopsies (eHiPCs) in patients undergoing coronary artery bypass grafting surgery [23]. We identified a subset of these eHiPCs that exhibit endothelial-like properties and are currently undergoing further characterization to determine their potential for revascularization.…”
Section: Systemic Effects Vs Cardiac Effectsdosing Considerationsmentioning
confidence: 99%
“…NRG-1 can also regulate angiogenesis via the prevention of apoptosis of endothelial progenitor cells [ 109 ]. We have recently demonstrated that human cardiac highly proliferative cells are characterized by the expression of all four ErbB receptors [ 110 ]. These cells are characterized by high proliferative activity in vitro , and have been shown to possess progenitor properties.…”
Section: Neuregulin In Repair Of Systolic Heart Failurementioning
confidence: 99%